#"factor the terms "color(blue)"by grouping"#
#=color(red)(x^2)(x-2)color(red)(+1)(x-2)#
#"take out the "color(blue)"common factor "(x-2)#
#=(x-2)(color(red)(x^2+1))#
#x^2+1" can be factored using "color(blue)"difference of squares"#
#a^2-b^2=(a-b)(a+b)#
#"with "a=x" and "b=ito(i=sqrt-1)#
#=(x-2)(x+i)(x-i)larrcolor(red)"in factored form"#
or
and bringing the common factor
solving the equation for
solving the equation for
graph{x^3-2x^2+x-2 [-10, 10, -5, 5]}
We will use a factoring method called grouping. If we group the first and the third and the second and the fourth together, each grout has its own greatest common factor:
Now we see another CF between the two terms :
How do you factory= -x^4 + x^3 + 3x^2 - 2x - 5